The TANTANGAN MENGINTEGRASIKAN ANAK-ANAK MIGRAN DI PENDIDIKAN ANAK USIA DINI INDONESIA DAN JERMAN - Gita Eva Nurjanah (Fakultas Tarbiyah IIQ Jakarta, 2026)
This study aims to compare the challenges of integrating migrant children into early childhood education (PAUD) in Indonesia and Germany. This study focuses on three main aspects, namely language, culture, and infrastructure. To obtain accurate results, this study uses a mixed approach, such as direct observation at PAUD institutions, interviewing teachers and parents, and reviewing various applicable policies. The results show that language difficulties are a common obstacle in both countries. However, there are differences in other challenges. In Indonesia, the main problem is the lack of resources and training for teachers who can teach in multiple languages. On the other hand, in Germany, the main challenge is cultural and social discrimination, even though the government provides stronger policy support for inclusion (Agustyaningrum & Himmi, 2022: 2105). To improve the inclusiveness of education for migrant children in early childhood education, this study recommends the development of bilingual programs, teacher training, and international cooperation. This also contributes to the formation of a more equitable global education policy (Nugroho & Prasetyo, 2022: 35). This study emphasizes that a holistic approach is needed to support the growth and development of migrant children in a multicultural environment.